2020
DOI: 10.1270/jsbbs.19167
|View full text |Cite
|
Sign up to set email alerts
|

A single QTL on chromosome 6DS derived from a winter wheat cultivar ‘OW104’ confers resistance to <i>Wheat yellow mosaic virus</i>

Abstract: Wheat yellow mosaic (WYM) is a soilborne disease caused by Wheat yellow mosaic virus (WYMV). Symptoms include yellow mosaic coloring of leaves, stunting, and growth inhibition. Severe infection may result in yield loss. WYM is one of the most serious diseases affecting wheat production in East Asia. The most effective control is through breeding resistant cultivars. A winter wheat cultivar, 'OW104', shows little to no symptoms in heavily WYMV-infested fields in Hokkaido, Japan. Here we detected Qym4, a QTL acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The product of the rym4/rym5 alleles is a translation initiation factor ( Stein et al 2005 ), while the resistance encoded by rym1/rym11 results from deletions in a gene encoding a protein disulfide isomerase-like protein ( Yang et al 2014 ). Following analysis based on the quantitative trait locus (QTL) approach, genes for resistance in bread wheat to WYMV have been mapped to regions on chromosome arms 2DL and 3BS ( Suzuki et al 2015 , Zhu et al 2012 ), 6DS ( Yamashita et al 2020 ) and the other chromosomes ( Jiang et al 2020 ), while a locus for resistance to WSSMV has been identified on chromosome arm 2DL ( Khan et al 2000 ). With respect to SBWMV, the presence of Sbm1 , a gene mapping to the distal end of the bread wheat chromosome arm 5DL, has been correlated with a measure of resistance ( Hao et al 2012 , Narasimhamoorthy et al 2006 ), with a smaller contribution from the chromosome arm 2BS locus Sbm2 ( Bayles et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The product of the rym4/rym5 alleles is a translation initiation factor ( Stein et al 2005 ), while the resistance encoded by rym1/rym11 results from deletions in a gene encoding a protein disulfide isomerase-like protein ( Yang et al 2014 ). Following analysis based on the quantitative trait locus (QTL) approach, genes for resistance in bread wheat to WYMV have been mapped to regions on chromosome arms 2DL and 3BS ( Suzuki et al 2015 , Zhu et al 2012 ), 6DS ( Yamashita et al 2020 ) and the other chromosomes ( Jiang et al 2020 ), while a locus for resistance to WSSMV has been identified on chromosome arm 2DL ( Khan et al 2000 ). With respect to SBWMV, the presence of Sbm1 , a gene mapping to the distal end of the bread wheat chromosome arm 5DL, has been correlated with a measure of resistance ( Hao et al 2012 , Narasimhamoorthy et al 2006 ), with a smaller contribution from the chromosome arm 2BS locus Sbm2 ( Bayles et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…S9 ). These 16 accessions were all able to limit viral replication, although it remains to be established whether either the mis-sense variant or the chimeric protein is responsible, since the accessions may also harbor other genes, such as Ym1 or Qym4 ( 28 ). The disease response of the 56 accessions which do not generate a 940-residue protein varied widely, implying the presence of genes for WYMV resistance other than CDS618.…”
Section: Resultsmentioning
confidence: 99%
“…Future development of new lines without linkage drag could become a powerful breeding tool for pyramiding resistance genes. Recently we started wheat breeding combining Qym1 and Qym2 with a new WYMV resistance gene at Qym4 derived from OW104 ( Yamashita et al 2020 ) in order to breed varieties with stronger resistance to WYMV. These approaches may help breeders respond to the ongoing changes in viral strains and climate.…”
Section: Discussionmentioning
confidence: 99%